PENERAPAN AGILE UNIFIED PROCESS DALAM PEMBANGUNAN SISTEM INFORMASI AKUNTANSI PENDAPATAN JASA - Syamsiah, Nurfia Oktaviani; Haryati, Tri (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2015)
Agile Unified Process (AUP) has been known as a suitable methodology for projects of software development of small to medium level. This methodology focuses on rapid iteration, release relatively small and often as possible, able to handle the changing needs of users, and involve users in the process of software development. However, little is known that the AUP can be effectively used for the requarement of the system needs less clear and less complete. This study reveals how AUP is a software development methodology that is most suitable for the needs of the system. At the beginning of the software development, it is very difficult for the client to specify what he needs. However, because the client is actively involved during the development of software, it can slowly improve the requarements of the system with the help of the development team. Phase in the AUP can be accurately followed and proved to be very useful and suitable for the requarements which less complete. The resulting software was successfully tested with the actual transaction. Design on a complete structured system while implementing only limited to the module and report only relates to the activities of service revenues. With the construction of this system expected revenue cycle services that exist in the company.Keywords: AUP, Accounting Information Systems, Revenue Cycle Services